Make a Match Type Cooperative Learning to Improve Mathematics Learning Outcomes - Siti Zumrotul Nikmah (Journal of Educational Analytics, 2022)
Mathematics is still considered a complicated and boring subject. So that a special method is needed to teach mathematics to make it an easy and fun lesson. One of the fun learning models is the make a match type cooperative learning model. This study aims to determine the type of cooperative learning make a match to improve mathematics learning outcomes in fourth grade students of MIN 1 Bener Meriah. The research method used in this research is classroom action research. The study was conducted in class IV MIN 1 Bener Meriah. Data collection techniques were carried out by observation, tests, and documentation. Then the data were analyzed using descriptive statistical analysis, namely statistics used to analyze the data by describing or describing the data collected as they are without intending to make conclusions that apply to the general public or generalizations. The results showed that there was an increase in student learning outcomes from pre-action, cycle I, and cycle II. The average value of the students' average score was 57.83 in the pre-action only 8 students who finished learning (22%). In the first cycle, the average value of the class increased to 67.81 and the number of students who completed was 21 students (58%). In the second cycle, the average value of the class increased to 75.86% and the number of students who completed was 33 students (92%).